Effect of kenaf fibre loading on thermal and dynamic mechanical properties of bio epoxy composites - Jawaid, Mohammad; Awad, Sameer; Ismail, Ahmad Safwan; Hashem, Mohamed; Fouad, Hassan; Uddin, Imran (Springer Science and Business Media, 2024)
Natural fibre-based polymer composites have better improvements owing to their thermal and mechanical properties besides environmentally friendly quality. In the present work, biocomposite fabricated at kenaf fibres (KF) loading (30, 40, 50, and 60 mass%) with bio epoxy matrix by the hot compression moulding method, and their thermal and dynamic mechanical characterisation were investigated and examined. This study was conducted to investigate the thermal behaviour through thermogravimetric analysis (TGA) and the derivative of thermogravimetric analysis (DTG: the maximum thermal decomposition; Tmax), dynamic mechanical analysis (DMA) and thermomechanical analysis (TMA). The presented findings from TGA and DTG curves showed that the thermal stability improved with increasing the KF loadings, as evidenced by the higher residual mass % and the lower mass loss %. On the other hand, it was found that the biocomposite sample (50 mass% KF) exhibited higher thermal stability up to 558.82 °C. Furthermore, the DMA findings obtained exhibited the greatest value of the storage modulus (E') with the following order of KF bio composite (KF-50 > KF-60 > KF-40 > KF-30). On the other hand, the values of loss modulus (E'') were increased as follows KF-30 > KF-40 > KF-50 > KF-60. However, the results showed that 50 mass% of KF into epoxy biocomposites recorded higher loss modulus value (323.56 MPa) among all other bio composite samples, while the values of tan δ were increased as follows: KF-30 > KF-40 > KF-50 > KF-60. The results obtained for the TMA revealed a better coefficient of thermal expansion (CTE) for the sample (KF-50) compared to other samples. © Akadémiai Kiadó, Budapest, Hungary 2024.